(untitled) (REMUNOM, 2024)
Prematurity represents a significant challenge in neonatology, impacting the health of newborns and requiring specialized care. It is defined as the birth of a baby before the completion of 37 weeks of gestation. This study investigates frequent complications in premature newborns and the crucial role of nursing in hospital care. The study focuses on identifying and analyzing the nursing practices that are most effective in caring for premature newborns. Through a comprehensive analysis, the most effective practices and the preventive role of the nursing team are highlighted. Prematurity is a complex phenomenon that requires a careful and specialized approach from healthcare teams, especially the nursing team. It is concluded that a multidisciplinary approach and evidence-based care are fundamental to improving health outcomes and quality of life for these vulnerable babies.